Peningkatan Komunikasi Matematis Serta Kemandirian BelajarSiswa SMA Melalui Strategi PQ4R Disertai Bacaan Refutation Text - Tandililing, Edy (Universitas Tanjungpura, 2011)
This study is experiment research with control group pre test- post test design and aimed to examine the influence of PQ4R strategy and Refutation Text, school level, and students mathematical prior knowledge toward achievement and enhancement of students mathematical communication ability and Self Regulated Learning. Subject of study as much as 241 students of class X from three Public Senior High Schools from high, medium and low school level. Research instrument consist of one set of students mathematical communication, and one set of students Self Regulated Learning scale. Data analysis use Kosmogorov-Smirnov Test (Tes-Z), Test Leven, Test-t, ANOVA one-way and two-way, Post Hoc Test (Scheffe) and also Chi-Square Test. The study found that learning with PR4R strategy accompanied by Refutation Text Reading give consistent influence compared with conventional learning influence whether is viewed as a whole, based on school level as well as mathematical initial knowledge. In addition, the study also found: (1) there is no interaction between learning (PQ4R) accompanied by Refutation Text reading and conventional) and school level toward (a) students mathematical communication and (b) students Self Regulated Learning; (2) there is no significant interaction between learning and students mathematical prior knowledge toward (a) students mathematical communication ability and (b) students Self Regulated Learning; and (3) there is association between students mathematical communication ability and students Self Regulated Learning. Keywords : PQ4R, refutation text, mathematical communication, self regulated learning